The effect of creating knowledge according to the model (Nonaka & Takeuchi, 1995) on organizational ambidexterity: A study on a sample of Iraqi private banks - Ahmed, Ahmed Hassan; Al-Kubaisi, Salah Al-Din Awwad (Journal of Economics and Administrative Sciences, 2021)
Purpose - This study relies on the descriptive and analytical approach through collecting and analyzing the necessary data, as this approach focuses on polling the opinions of the research sample and its directions, and aims to develop a model that studies the relationship between knowledge creation and organizational ambidexterity in Iraqi private banks and verifying its validity experimentally.Design / Methodology / Introduction - A survey was conducted through a questionnaire form to collect data from a sample of (113) managers in private commercial banks. In addition, this study used the AMOS program and the ready-to-use statistical program package (SPSS V.25) to test the proposed hypotheses of the theoretical model experimentally.Results - The results show that knowledge creation has a significant and positive indirect effect on stimulating organizational ambidexterity in private commercial banks through its effect on exploiting opportunities in the workplace and exploring opportunities in the external environment of banks.Practical effects - to improve knowledge creation, bank management must pay more attention to it as a strategic resource to create wealth and added value to enable organizations to grow and survive through training courses, holders of higher degrees and attract knowledge expertise in addition to the need to maximize cultural awareness towards improving the organizational ambidexterity of banks, especially in Exploiting the bank's internal opportunities, both material and human, according to the current circumstances, through rewards moral and material incentives. Originality / Value - This study complements and advances previous research on knowledge creation in several ways. First, the current study proposes a conceptual model that illustrates the interrelationships between the main variables in Iraqi private banks. Second, this study explores the role of organizational ambidexterity that benefits from exploiting and exploring opportunities in the context of knowledge acquisition, accumulation and exchange. Thus, overcoming the challenges associated with creating knowledge.